Building a Harmonious Family in the Qur'an: An Analysis of Sternberg's Theory of Love on Household Harmony - Anam, Hairul; Bakar, Abu (TAFSE: Journal of Qur'anic Studies, 2024)
Family harmony is a fundamental human aspiration, significantly impacting the religious and educational development of children as they witness their parents' lives. This study explores the construction of a harmonious family according to the Qur'an, using Sternberg's love theory, which posits that an ideal marriage is built on three components: intimacy, passion, and commitment. Similarly, the Qur'an describes a harmonious family through the concepts of sakinah, mawaddah, and rahmah. This research is a library research study, utilizing data from various books and literature. The descriptive-analytical approach is employed to present and analyze the data in alignment with the Qur'an. The findings reveal that Sternberg's love theory aligns with the Qur'anic perspective on maintaining a healthy family sexual relationship, illustrated by the components of intimacy and passion, as reflected in the Qur'anic verses Al-Baqarah 2:223, An-Nisa' 4:19, and Al-Baqarah 2:187. These verses underscore the significance of sexual relations within the family. Additionally, the commitment component corresponds to the union of husband and wife in all matters, as depicted in An-Nisa' 4:1.